Luciano Segreto, Carles Manera Erbina, Manfred Pohl (Eds.): Europe at the Seaside. The Economic History of Mass Tourism in the Mediterranean. New York, Berghahn Books, 2009, 304 págs. - Tascón Fernández, Julio (Investigaciones de Historia Económica, 2019)
Sin resumen